Integrating Character Education Into the RECE Learning Model Through Pancasila and Citizenship Education Subjects - Sarkadi,; Casmana, Asep Rudi; Hisyam, Ciek Julyati; Wardatussa'idah, Indah (Frontiers in Education, 2022)
This study aimed to investigate teaching character education values using the RECE (reflective, engage, collaborative, and elaborative) model. In Indonesia, Pancasila and Citizenship Education Subjects are mandatory programs that must be incorporated into each activity in schools, either through particular programs or the subjects taught. The civic education module taught in schools has a wider responsibility to teach character education. Currently, this module focuses on theory and encourages students to learn about character. Although teachers can use a wide variety of learning models for teaching character, this study uses a qualitative and descriptive approach focused on exploring the RECE teaching model. This method enables researchers to go to classrooms and observe how teachers impart character education. In total, 15 respondents participated in this study. Of these, three were citizenship education teachers, one was a vice-principal, one was a school principal, and ten were senior high school students in Jakarta. To obtain data, in-depth interviews were used along with 135-min long focus group discussions with all participants. The data were then analyzed using the content analysis method and nVivo software. The results showed that students can reflect, elaborate, collaborate, and communicate well when learning character education in school. The four stages of teaching character education were successful in integrating values in the classroom. This study has implications for the teachers who impart character education.